Methyl Jasmonate Induces Papain Inhibitor(s) in Tomato Leaves. - Bolter, C. J. (1993)
Leaves of 18- to 24-d-old tomato (Lycopersicon esculentum) plants exposed to gaseous methyl jasmonate (MJ) for 24 h at 30[deg]C in continuous light contained high levels of soluble protein that inhibited papain. Chromatographic analysis demonstrated that the active protein had a molecular mass of 80 to 90 kD. Induction of papain inhibitor was directly related to the concentration of air-borne MJ up to a maximum of 0.1 [mu]L MJ per treatment and depended on the duration of exposure up to 18 h. Inhibitor activity in plants treated for less than 18 h increased with time after treatment. Levels remained constant for up to 4 d after treatment, after which time activity decreased. The youngest leaf, leaf 5, consistently lost activity at a faster rate than older, lower leaves. Inhibitor concentration in all leaves was reduced to minimum levels by 11 d after MJ treatment, but did not return to control levels. Treatment with MJ in the dark did induce inhibitor activity, but at a significantly lower rate. Polyclonal antibodies raised to purified potato tuber skin cysteine proteinase inhibitors (CPI) cross-reacted with the tomato inhibitor, suggesting that the tomato papain inhibitor and the potato CPI are closely related. No papain inhibitor activity was observed in extracts from wounded tomato leaves, nor was there any immunoreactivity with antibodies raised to potato tuber skin CPI.